Comparison of Linear and Nonlinear Optimization Methods of Heating Plant Operation - Muskat, Peter; Urban, Frantisek; Bereznai, Jozef; Zavodny, Zdenko (Manufacturing Technology Journal, 2016)
The article presents comparison of optimization methods applied to operation of the heating plant. Optimizing problems are possible to solve with using of methods of the linear programming (LP) or nonlinear programming (NLP). In the paper method of differential addition (LP, NLP), method of characteristics (LP), simplex method (LP), method of Lagrange multipliers (LP, NLP) and method of hyperplane in n - dimensional space (LP, NLP) are presented from point of view of requirements for designing and modifications of the program, requirements on system memory and computation time, comparison of the optimizing methods for loading of the thermal power machines and devices.
Keywords: heat source; optimizing criterion; optimizing methods; heat source operation; fuel costs